The Eclectic Visual Culture of Medieval Moldavia - Sullivan, Alice Isabella, author.
1 online resource (528 pages)
Keywords: Medieval Moldavia - which was located within present-day northeastern Romania and the Republic of Moldova - developed a bold and eclectic visual culture beginning in the 15th century. Within this networked Carpathian Mountain region, art and architecture reflect the creativity and diversity of the cultural landscapes of Eastern Europe. Moldavian objects and monuments - ranging from fortified monasteries and churches enveloped in fresco cycles to silk embroideries, delicately carved woodwork and metalwork, as well as manuscripts gifted to Mount Athos and other Christian centers - negotiate the complex issues of patronage and community in the region. The works attest to processes of cultural contact and translation, revealing how Western medieval, Byzantine, and Slavic traditions were mediated in Moldavian contexts in the post-Byzantine period. .